Calculation of Losses and Temperature Rise for High Frequency Transformer under Forced-air Convection - Chang, Ren-Chun; Chen, Chien-Kuo; Wang, Chien-Yue; Tzou, Ying-Yu (My University, 2010)
This paper presents a method for loss calculation, including core losses and winding losses, and temperature rise in high frequency transformer design under forced-air convection. Analytical models of winding losses for multiple-layer copper foil and Litz wire windings with MMF boundary conditions have been developed. Geometric parameters of conductor and distribution of magneto-motive forces are considered in the formulation of the winding loss equations. Comparing with the FEM simulation result, it shows that these two models can achieve good accuracy. The core losses were calculated using modified Steinmetz equation (MSE), which has been validated for power ferrite material. The winding loss models, including copper foil model and Litz wire model, were developed for multiple-layer with magneto-motive forces boundary conditions. To verify the accuracy of these two models, the 2D FEM simulation was used for comparison, and the errors of copper foil model and Litz wire model were within 1% and around 5%similar to 9%, respectively. The 5-R modified model for E-type core was presented as 5 resistors by thermal network to evaluate temperature rise under forced-air convection, and the heat transfer coefficients and material properties were obtained using thermal measurement in wind tunnel.
Keywords: Winding losses; Copper foil; Litz wire; MMF; Multiple-layer